PHOTOCATALYTIC DEGRADATION AND ADSORPTION OF REMAZOL DYE WASTE USING TIO₂/BIOCHAR COMPOSITE AT SMAN 3 MUARO JAMBI BATIK STUDIO - Mutia Hasmi Pradila; Muhammad Damris; Maison Maison (Physics Education Departement, Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2025)
This study aims to evaluate the effectiveness of Remazol batik wastewater treatment at SMAN 3 Muaro Jambi through degradation and adsorption using a TiO₂/biochar photocatalytic composite. The biochar was derived from cassava peel and employed under UV light irradiation, with UV-Vis spectrophotometry used for analysis. Treatment efficiency was assessed by varying the biochar mass (1–4 grams) and reaction time (1, 3, and 6 hours). The highest removal efficiency of 100% was achieved at 4 grams of biochar and 6 hours of exposure. The adsorption process followed the Freundlich isotherm model, indicating a multilayer adsorption mechanism on the biochar surface. These findings suggest that the TiO₂/biochar composite offers an effective, eco-friendly, and practical solution for small-scale batik wastewater treatment, particularly in educational and home industry settings.